The Chile-2015 (Illapel) earthquake and tsunami - Braitenberg, Carla; Rabinovich, A. B. (Springer International Publishing, 2017)
This volume presents a collection of contributions that were published in "Pure and Applied Geophysics - pageoph" and which deals with the major earthquake that hit Illapel, Chile on September 16, 2015 with magnitude 8.3, and associated trans-oceanic tsunami. The subducting Nazca plate beneath the Andes caused this major earthquake, generating strong shaking, permanent deformation, free oscillations of the Earth, and tsunamis. This event occurred in the flat-angle subducting segment of the plate. The generated tsunami spread throughout the entire Pacific Ocean and was recorded by numerous coastal tide gauges and open-ocean DART stations. All articles give an up-to-date account of research in one of the most active seismic zones worldwide. An introductory article by Kenji Satake rounds this collection off.
3. Truncated Lévy Flight Model.
Keywords: 2000-2099; Earthquakes -- Chile -- Illapel -- 21st century.; Tsunamis -- Chile -- Illapel -- 21st century.; Chile -- Illapel.; elektronické knihy; electronic books